2014 IEEE International Conference on Computational Photography (ICCP) 2014
DOI: 10.1109/iccphot.2014.6831800
|View full text |Cite
|
Sign up to set email alerts
|

Can we beat Hadamard multiplexing? Data driven design and analysis for computational imaging systems

Abstract: Computational Imaging (CI) systems that exploit optical multiplexing and algorithmic demultiplexing have been shown to improve imaging performance in tasks such as motion deblurring, extended depth of field, light field and hyper-spectral imaging. Design and performance analysis of many of these approaches tend to ignore the role of image priors. It is well known that utilizing statistical image priors significantly improves demultiplexing performance. In this paper, we extend the Gaussian Mixture Model as a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Mitra et al 5 take this even further and compute illumination patterns using an optimization based on image priors. In contrast to previous methods, their method is able to handle large amounts of light, but it still relies on the assumption of a one-dimensional affine noise model.…”
Section: Plenoptic Multiplexingmentioning
confidence: 99%
“…Mitra et al 5 take this even further and compute illumination patterns using an optimization based on image priors. In contrast to previous methods, their method is able to handle large amounts of light, but it still relies on the assumption of a one-dimensional affine noise model.…”
Section: Plenoptic Multiplexingmentioning
confidence: 99%
“…Contrary to compressive computational imaging, MSFA offers a very time efficient option for spectral reconstruction. Recently, it has been shown that, when using wide-band filters, MSFA based methods can be more accurate in the common case where the “photon to read noise ratios” (PRR) is not very low [ 11 ]. Therefore, various multi-channel spectral imaging system with MSFA have been designed recently.…”
Section: Related Workmentioning
confidence: 99%
“…The coded apertures for super-resolution on the other hand, permit high resolution reconstructions from a low-resolution compressive measurement set. A data driven coding scheme is introduced in [8], in which a prior model of the scene is used, yet it has not been tested in CASSI. In this paper, a new family of coded aperture patterns named the SUM codes is introduced.…”
Section: Introductionmentioning
confidence: 99%